Design is real, complex, inclusive, emergent and evil. (March 2020) - Karakiewicz, Justyna
Can computers make our designs more intelligent and better informed? This is the implication of the theme of the special issue. Architectural design is often thought of as the design of the object, and design models of architecture seek to explicate this process. As an architect, however, I cannot subscribe to that view. In this particular article, I will explore how computational approaches have illuminated and expanded my work to enable the interaction of these themes across scores of projects. Underpinning the projects are foundational concepts: design is real, complex, inclusive, emergent and evil. Design is grounded in reality and facts, that we can derive design outcomes from a deep and unblemished understanding of the world around us. It is not a stylistic escape. Reality is complex. Architectural design has sought to simplify. This was inescapable when projects are so large yet need to be communicated succinctly. 'Less is more' justified this approach. In town planning, this is evident in the tool of zoning. Parse the problem and then address each piece. What we do is part of a larger effort. The field of architecture seeks distinction. Design theories want to distinguish and elevate architecture. But if design is complex and it is real, then it is tied to messy realism. Designing has to become accessible to other realms of knowledge. Designing is the seeking of opportunity. For many, design is simply finding the answer – think of Herbert Simon's statement that design is problem solving. Design reveals opportunities, and these emergent conditions are to be grasped. As designers, our decisions have implications. We know now that what we build has future implications in ways that are profound. When we define design as problem solving, we ignore the truth that design is problem making.